2020
DOI: 10.5194/amt-2020-404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of Aeolus winds using radiosonde observations and NWP model equivalents

Abstract: Abstract. In August 2018, the first Doppler Wind Lidar, developed by the European Space Agency (ESA), was launched on board the Aeolus satellite into space. Providing atmospheric wind profiles on a global basis, the Earth Explorer mission is expected to demonstrate improvements in the quality of numerical weather prediction (NWP). For the use of Aeolus observations in NWP data assimilation, a detailed characterization of the quality and the minimization of systematic errors is crucial. This study performs a st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…This is further depicted in the profile comparison (Figure 16c , it should be noted here that the validated Aeolus L2B dataset is known to contain wind speed biases caused by an imperfect telescope temperature management along the orbit and from orbit to orbit, pending the top of the atmosphere total radiance variability. This has been shown from ECMWF model observation monitoring and from comparisons with ground-based and radiosonde observations (Martin et al 2020). These results differ from those reported by Witschas et al (2020) during WindVal III and AVATARE, which could be caused by a variety of factors including differences in Aeolus laser pulse energy and latitude, longitude, and time-dependent telescope temperature issues at the time of the campaigns, wind conditions being sampled, sample size, and criteria used to construct the Aeolus -airborne wind lidar match database.…”
Section: Dawn Comparisons With Aeolusmentioning
confidence: 68%
See 1 more Smart Citation
“…This is further depicted in the profile comparison (Figure 16c , it should be noted here that the validated Aeolus L2B dataset is known to contain wind speed biases caused by an imperfect telescope temperature management along the orbit and from orbit to orbit, pending the top of the atmosphere total radiance variability. This has been shown from ECMWF model observation monitoring and from comparisons with ground-based and radiosonde observations (Martin et al 2020). These results differ from those reported by Witschas et al (2020) during WindVal III and AVATARE, which could be caused by a variety of factors including differences in Aeolus laser pulse energy and latitude, longitude, and time-dependent telescope temperature issues at the time of the campaigns, wind conditions being sampled, sample size, and criteria used to construct the Aeolus -airborne wind lidar match database.…”
Section: Dawn Comparisons With Aeolusmentioning
confidence: 68%
“…Finally, comparisons of the Aeolus data quality with the ECMWF model background and collocated CAL/VAL observations from ground-based instrumentation (including wind profilers and radiosondes) showed that the variability of the Earth top-of-atmosphere total radiance along the Aeolus orbit cause thermal stress an deformations of the instrument telescope which could not be fully compensated by the implemented telescope thermal control. This has caused biases of the Aeolus L2B winds of several m/s varying along the orbit and from orbit to orbit (Martin et al 2020). An on-ground correction of the telescope temperature induced bias has been developed and was implemented in April 2020.…”
Section: Aeolusmentioning
confidence: 99%
“…In addition, it should be noted that RS has the problem of time and space drift in measuring the vertical wind profile (Baars et al, 2020;Martin et al, 2020). As shown in Fig.…”
Section: Aeolus and Rs Datamentioning
confidence: 99%
“…Moreover, the Aeolus wind products have been compared with RS data above the Atlantic Ocean, from which the systematic and statistical errors of the Rayleigh (Mie) winds were found less than 1.5 (1.0) and 3.3 (1.0) m/s, respectively (Baars et al, 2020). Martin et al (2020) compared the Aeolus winds with radiosonde (RS) observations and two numerical weather prediction model equivalents, confirming that the performance of Aeolus wind products can be easily affected by satellite flight direction, seasonal differences and geographic changes. In addition, Guo et al (2020) evaluated the performance of Aeolus wind products over China by comparing with data from the ground-based radar wind profiler network of China.…”
Section: Introductionmentioning
confidence: 99%
“…On 9 January 2020, the operational assimilation of the Aeolus wind data started at the European Centre for Medium-Range Weather Forecasts (ECMWF), followed by the German, French, and British weather services Deutscher Wetterdienst (DWD), Météo France, and Met Office in May, June, and December 2020, respectively. Recent assessments of the significance of the Aeolus data for NWP have demonstrated statistically positive impact, especially in the tropics and at the poles, thus providing a useful contribution to the GOS (Rennie and Isaksen, 2020a;Rennie and Isaksen, 2020b;Martin et al, 2020). This was made possible by the identification of and correction for large systematic errors which had strongly degraded the wind data quality in the initial phase of the mission (Kanitz et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%